Comparative Study of Cycle Threshold RT-PCR SARS Cov-2 between Saliva Specimen and Nasopharyngeal Swab - Indriana Citraningtyas; Tjie Kok (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Coronavirus Disease 2019 (Covid-19) is an infectious disease that spreads quickly and attacks the respiratory system that can causing death. The main diagnosis of Covid-19 is conducted by a nasopharyngeal swab, an invasive method which can in turn increase the risk of transmission from patient to swabber, and cause discomfort for the patient when nasopharyngeal swab was collected. Hence, there is a need for non-invasive methods development, one of which is using saliva specimens. This study aims to evaluate the potential of using saliva specimens for diagnosis as an alternative to nasopharyngeal swabs. The study was conducted on confirmed patients at Hajj Dormitory Embarkation Surabaya using an analytical experimental research design. The samples were collected by simple random sampling from 35 patients at Hajj Dormitory Embarkation Surabaya who meet the inclusion criteria, and evaluated at Surabaya Regional Health Laboratory using RT-PCR (Real Time Polymerase Chain Extraction). The results showed that there was no significant difference between the cycle threshold RT-PCR of nasopharyngeal swab and saliva specimen, for target E Gene, OrF1ab Gene, and N Gene. The sensitivity and specificity of saliva specimens are 88.2% and 100%, respectively, from nasopharyngeal swabs. Hence, saliva specimen has the potential to be used as a non-invasive method for Covid-19 diagnosis and for patient comfort.